Searching for an OxChain: Co-designing blockchain applications for charitable giving. Issue 1 (1st November 2019) - Elsden, Chris; Symons, Kate; Speed, Chris; Vines, John; Spaa, Anne
AbstractThe OxChain project is investigating the design of blockchain applications in partnership with a large and traditionally trusted institution, Oxfam. We outline some of the potential opportunities that distributed ledger technologies could offer the charity and development sector as a whole, but focus on the challenges of undertaking co-design work in the context of large institutions. We suggest the need to leverage existing trusted relationships and understand the unique value that such institutions offer.